Clinical analysis of atlanto-occipital decompression in the management of chiari malformation with multi-segmental syringomyelia - Sun, Yaning; Fang, Jiangshun; Wang, Shengjuan; Luan, Jimei; Wang, Na; Lv, Lige; Xin, Chaojun; Luo, Pengyuan; Yue, Yanke; Cheng, Zhenghai; Yang, Zhiguo; Chen, Liuyin (Frontiers in Pediatrics, 2024)
Chiari malformation type I with syringomyelia (CM-I-S) is a very common disease in neurosurgery. There are various surgical methods. But it is controversial. There are few reports about children, especially the treatment of multi-segmental beaded syringomyelia. The purpose of this study was to explore the clinical effects of atlanto-occipital decompression (AOD) in the management of Chiari malformation type I (CM-I) with multi-segmental beaded syringomyelia(MSBS) in pediatric patients.This retrospective study were pediatric patients with CM-I combined with MSBS who were treated in our hospital from January 2015 to December 2023. The patients who received the AOD treatment were screened according to inclusion and exclusion criteria. Outcomes were assessed by comparison of pre-and postoperative clinical, Chicago Chiari Outcome Scale (CCOS), the diameter and volume of the syringomyelia, morphological parameters of posterior cranial fossa (cervical spinal cord angle of medulla oblongata, CSC-MO) and complications in the enrolled children.This study ultimately included 21 pediatric patients with CM-I and MSBS. All the patients successfully completed the operation, which consists of atlanto-occipital decompression, partial resection of the posterior arch of the atlas, electrocoagulation of the cerebellar tonsil, pseudomembrane resection of the central canal orifice (latch) of the spinal cord, and artificial dura mater expansion repair. No death, no relapses, no serious neurological dysfunction and other complications. At the last follow-up, the clinical symptoms of patients basically disappeared. The results of magnetic resonance imaging (MRI) showed that the average preoperative cerebellar tonsillar hernia was 12.4±4.6mm, and the postoperative were all above the foramen magnum. The average preoperative syringomyelia volume was 11.7±3.7cm2, and the syringomyelia disappeared or significantly shrunk after operation, with the volume unable to be accurately measured. The median preoperative CSC-MO was 132.5°, and the median postoperative CSC-MO was 150°, with a significant difference. The median preoperative pain and non-pain score of CCOS was 4 and 3 respectively. The symptoms disappeared after operation, and the score was 4. Only 5 children had cerebrospinal fluid leakage.The AOD is safe and effective in CM-I with MSBS in pediatric patients. Pseudomembrane resection of the central canal orifice (latch) of the spinal cord is crucial for the treatment of syringomyelia.